Myocardial Function Pre- and Post-Fetal Endoscopic Tracheal Occlusion (FETO) in Fetuses with Left-Sided Moderate to Severe Congenital Diaphragmatic Hernia - Degenhardt, Jan; Enzensberger, Christian; Tenzer, Aline; Kawecki, Andrea; Kohl, Thomas; Widriani, Ellydda; Axt-Fliedner, Roland (Ultraschall in der Medizin - European Journal of Ultrasound, 2017)
Purpose To evaluate pre- and postprocedural myocardial function in fetuses with moderate to severe congenital diaphragmatic hernia (CDH) who underwent FETO to improve survival and to reduce morbidity and to compare these data with fetuses and CDH not undergoing FETO and normal controls.Materials and Methods 8 fetuses with isolated left-sided CDH were included and underwent FETO at our center between 2012 and 2013. Prior to and after the operation, myocardial function was assessed by measuring the mitral annular plane systolic excursion (MAPSE), the tricuspid annular plane systolic excursion (TAPSE), Tei index, isovolumetric contraction time (ICT), ejection time (ET), isovolumetric relaxation time (IRT) for the left ventricle in PW Doppler ultrasound as well as ICT, ET, IRT and Tei index in pulsed wave tissue Doppler imaging (PW-TDI) for the left and right ventricle. The E-, A-, E’- and A’-wave peak velocity and the systolic downward motion (S’) were measured for both ventricles and the E/A, E/E’ and E’/A’ ratios were calculated.Results were compared to fetuses with CDH not undergoing FETO and to gestational age-matched healthy controls. Results: FETO was performed at 32.5 (SD 2.4) weeks of gestation. There was no statistically significant change in myocardial function in fetuses treated by FETO except a slight prolongation of the ICT of the left ventricle in PW-TDI. The myocardial function of fetuses with CDH pre- and post-FETO and fetuses with CDH without FETO was comparable to that of healthy controls.Conclusion In our series FETO did not affect myocardial function in fetuses with left-sided CDH. Although ventricular preload increases, FETO seems to have no short-term impact on fetal myocardial performance.
Keywords: FETO; diaphragmatic hernia; myocardial function